Hits and misses: the high's and low's of sportswriting in the Philippines a historical study of print sports journalism in the Philippines from 1990 to 2005 - Campos, Kirk Maurice R.
" Sports is an essential part of human culture. Not only does it improve physical well-being but it also enhances mental prowess and social involvement. This fact is very evident in the Philippines. The Philippines is a sporting nation. Millions of Filipinos participate in sporting activities for the thrill of competition and fun. Others stay at the sidelines and watch the action to be entertained. Sports is a staple media product that has a very huge market. It is in this respect that covering sports is an important part of journalism for its caters to mass audiences. Being a specialized field of journalims, sports journalism has the capacity to influences and educate its audience. It is essential that sports journalism be developed, analyzed and studied to be able to protect its audience. The study tried to probe into the current situation of print sports journalism in the country by tracing its roots through bibliographic research. Focus interviews were also conducted with veteran sports journalists who have covered the beat to substantiate the real situation of sports journalism in the country. Current sports trends for the period 1990 to 2005 were also observed through the coverage of the leading broadsheets Manila Bulletin, Philippine Daily Inquirer and Philippine Star and leading sports magazine Atlas Sports Magazine. Training in the field was also evaluated by analyzing the curricula of nine universities and colleges in Metro Manila that offer courses in Journalism or Mass Communication. Through these methods, it was found out that print sports journalism in the Philippines is on a steady decline. This was brought about by many factors. 1) The market's fixation on basketball. Much attention was devoted to basketball, by sportwriters and by sports organizations, to the point that many local sports were neglected by sports organizations and the government. 2) The advent of technology. technology diverted the interest of audiences to other mediums, such as television and the internet, leaving the print medium as a last source of information. Technological advancements also prompted sportswriters to be lax in their reportage. 3) The decline of sports publications. There was a massive decline of sports magazine and publications through the years that caused the lack of interest of audiences in the medium. 4) The lack of support from sportswriting associations. Associations of sportswriters were merely social organizations and lacked responsibility and improving the craft among their members. 5) The diminishing quality of reportage. Because of sportswriters' reliance on press releases, result-oriented reporting and lack of interest in offering in-depth sports articles. 6) The lack of academic training in sportswriting."